RIWAYAT KEKURANGAN ENERGI KRONIS PADA KEHAMILAN SEBAGAI PREDIKTOR KEJADIAN STUNTING PADA ANAK: SISTEMATIK REVIEW - Muchtar, Febriana; Salma, Wa Ode (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
The government is currently concerned about stunting. Stunting, often known as "short" toddler, is a failure of growth in infants caused by persistent nutritional issues, in which the baby is malnourished for 1000 days of his or her life. When they grow up, the stunting that happens will be detrimental. The goal of this research was to see if there was a link between chronic energy shortage in pregnant mothers and child stunting. The sample of this research is mother and or child. Writing this literature review is based on research articles/journals using an observational study design; case control and cohort. The data base involved is Google Scholar which is used as the main source of data search in writing this research. Search literature using keywords: “stunting, history of chronic energy deficiency, pregnant women. The literature/articles accessed are published in Indonesian. Screening is carried out in taking literature materials that are considered appropriate and relevant to the title being studied. The literature taken is published for the period between 2016-2021. The results of the literature search have found a lot of literature from national and Indonesian-language journals, as many as 2,210. After screening, it was found that 1,101 articles did not have the full text because they were in the form of a repository or digital library, and could not be accessed, 310 articles had a variable scope not a history of chronic energy deficiency in pregnancy, there were 35 articles in the form of theses and theses, so that after being filtered and declared eligible, the remaining 12 articles.